2009
DOI: 10.3109/00365540903362501
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Crimean-Congo haemorrhagic fever in livestock and ticks in Ardabil Province, Iran during 2004–2005

Abstract: Crimean-Congo haemorrhagic fever (CCHF) is a viral haemorrhagic fever caused by the CCHF virus. It is mainly transmitted to humans and animals by ticks. In recent y, large numbers of livestock have been transported across the border areas of Ardabil Province resulting in an outbreak of CCHF in the adjacent districts. A comprehensive study was carried out to assess the epidemiological aspects of the disease in this province. In the study area, 130 ticks were collected from randomly selected villages and classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 13 publications
5
33
2
Order By: Relevance
“…One possible reason for the lower prevalence of infection in cattle (13.0%) could be the low frequency of pasture usage of dairy cattle in the region; however, small ruminants are continuously in the pasture during the season. In accordance with our results, similar studies (7,12,14,15,18) confirmed that the CCHF antibody prevalence is generally higher in small ruminants than cattle. Although there are no similar data from Turkey to compare the results, very limited surveys were conducted in the endemic region.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One possible reason for the lower prevalence of infection in cattle (13.0%) could be the low frequency of pasture usage of dairy cattle in the region; however, small ruminants are continuously in the pasture during the season. In accordance with our results, similar studies (7,12,14,15,18) confirmed that the CCHF antibody prevalence is generally higher in small ruminants than cattle. Although there are no similar data from Turkey to compare the results, very limited surveys were conducted in the endemic region.…”
Section: Discussionsupporting
confidence: 93%
“…Different serological results have been reported in livestock animals in various countries, i.e., 57.7% in Niger (11), 39.3% in Iran (15), and 3.13% in Egypt (12). The overall seroprevalence rate of 33.1%, which is comparable to some previous studies (18), indicates that CCHF virus infection is moderately distributed throughout the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…CCHF antibodies were detected in 5.9% of sampled cattle in Iran (Lotfollahzadeh et al, 2011). Differences were observed for the sero-prevalence in various livestock species in many studies (Mariner et al, 1995;Hassanein et al, 1997;Mohamed et al, 2008;Telmadarraiy et al, 2010;Albayrak et al, 2012;Adam et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Many authors have documented the antigen detection in ticks collected in various regions of the world through similar methods (Telmadarraiy et al, 2010;Albayrak et al, 2012;Estradapena et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Sporadic outbreaks of CCHF have been reported from Kosovo, Senegal, Turkey, Bulgaria, Iran, Pakistan, and Mauritania (2,(7)(8)(9). The predominant hosts of CCHFV include wild and domestic mammals and birds.…”
Section: Introductionmentioning
confidence: 99%